2011
DOI: 10.1590/s1807-59322011001200008
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sensory integration affects balance control in hemiparetic patients within the first year after stroke

Abstract: OBJECTIVE:Impairments in balance can be a consequence of changes in the motor, sensory, and integrative aspects of motor control. Abnormal sensory reweighting, i.e., the ability to select the most appropriate sensory information to achieve postural stability, may contribute to balance impairment. The Sensory Organization Test is a component of Computerized Dynamic Posturography that evaluates the impact of visual, vestibular, and somatosensory inputs, as well as sensory reweighting, under conditions of sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
19

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 30 publications
4
62
0
19
Order By: Relevance
“…A previous study adopting a similar assessment in 21 ST subjects showed that sensory impairments significantly impact balance and were related to history of falls (50). Our results on a larger sample suggest that alteration of a single sensory input had a small though significant impact on balance control on the AP axis.…”
Section: Balance Strategies During Alteration Of Sensory Inputsupporting
confidence: 61%
“…A previous study adopting a similar assessment in 21 ST subjects showed that sensory impairments significantly impact balance and were related to history of falls (50). Our results on a larger sample suggest that alteration of a single sensory input had a small though significant impact on balance control on the AP axis.…”
Section: Balance Strategies During Alteration Of Sensory Inputsupporting
confidence: 61%
“…CDP is a quantitative method used to evaluate and treat balance disorders (Sturnieks et al, 2008;Oliveira et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Healthy individuals show comparatively limited after-effects not because they do not adapt and learn the task as well as less healthy individuals. Healthy individuals show limited after-effects because they possess the flexibility to adapt to the overground (non-split belt) environment as soon as is presented by efficiently and flexibly readjusting sensory gains based on environmental conditions; an ability significantly reduced in PD patients (Scocco et al 2014), stroke survivors (Oliveira et al 2011) and individuals exposed to extreme sensory conditions (Speers et al 1998). In fact, this particular study was performed because certain healthy individuals (i.e.…”
Section: Discussionmentioning
confidence: 99%